Inadequate Facilities and their Impact on Learning: Voices of University Students in District Gwadar - Rizwana Ibrahim; Rabia Aslam (Indus Journal of Social Sciences, 2025)
This study investigates how students' learning at the University of Gwadar is affected by subpar facilities. The main goal was to comprehend how students' academic performance is impacted by inadequate infrastructure, poor teaching methods, a lack of a conducive learning environment, a lack of research resources, and other associated problems. Five respondents participated in this qualitative study, and theme analysis was used to examine the data. Five main themes emerged from the findings:(1) problems with resources and infrastructure, (2) difficulties with the teaching and learning process (3) learning environment and student support; (4) obstacles to academic development and research; and (5) results and effects on students' learning. The findings show that insufficient facilitators not only interfere with the learning process but also consume a detrimental influence on scholars' academic presentation, motivation, too mental health. To guarantee high-quality higher education, the study suggests rapid improvements in foundational education, improved teacher preparation, and more research opportunities.